Rapidly-cured two-component heat-conducting pouring sealant and preparation method thereof
By using two-component thermally conductive potting adhesives prepared with epoxy-based silicone oil and other materials, the existing potting adhesives have solved the problems of deactivation of active catalysts and poor adhesion during the curing process, and the improvement of rapid curing, low VOC emissions and multifunctional performance has been achieved.
Patent Information
- Application Number
- CN202411978655.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
During the curing process, existing addition molded and condensation potting glues have problems such as deactivation of active catalysts, poor adhesive applicability, poor mechanical properties after curing, and incomplete VOC emissions, which affect electrical insulation and industrial production efficiency.
Two-component thermal potting adhesive is prepared by reacting epoxy silicone oil, crosslinking agent, plasticizer, thermal conduction powder, reinforcement, coupling agent and catalyst. Alumina with different particle sizes and shapes is used as thermal filler, and the adhesiveness and compatibility are improved by using silane coupling agent.
It achieves rapid curing, good adhesion, thermal conductivity, electrical insulation and low VOC emissions. It is suitable for bonding of various materials and meets GB/T13477.20-2002 and RoHS/REACH standards.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer sealing materials, and in particular to a fast-curing two-component heat-conducting potting glue and a preparation method and application thereof. Background Art
[0002] In recent years, industries such as electronic products and new energy vehicles have developed rapidly, and the application of potting compounds in electronic components and power modules has gradually increased. In the process of product iteration and upgrading, major manufacturers have gradually increased their requirements for the application of potting compounds. In order to meet customers' various requirements for potting compounds, the industry has also conducted a lot of research on potting compounds, among which silicone potting compounds are one of the focuses.
[0003] Silicone potting glue is currently divided into addition potting glue, condensation potting glue, etc., which have excellent electrical insulation performance and high thermal conductivity. However, addition potting glue still uses Perkin compound as catalyst, which has high activity and is sensitive to many external compounds. It is easy to be deactivated after contact, resulting in the phenomenon that the glue sample does not solidify. Moreover, addition potting glue has low bonding applicability to materials and is difficult to bond to many materials, so it is difficult to pass the waterproof grade test.
[0004] The condensation-type two-component potting glue relies on water molecules in the air to cure, which has a certain impact on the depth of curing. The mechanical properties after overall curing are poor. In addition, affected by the density of the glue after overall curing, there is still a small amount of VOC that has not been discharged inside the condensation-type two-component potting glue after overall curing, which has a certain impact on electrical insulation. This emission takes time and also affects industrial production efficiency. Summary of the invention
[0005] The present invention is achieved through the following technical solutions:
[0006] The invention adopts epoxy silicone oil, crosslinking agent, plasticizer, thermal conductive powder, reinforcing agent, coupling agent and catalyst to react and prepare the product.
[0007] The potting glue described in the present invention is a two-component glue sample with a mass ratio of 1:1, using epoxy silicone oil and a cross-linking agent as basic reactants, using alumina of different particle sizes and shapes as thermal conductive fillers, and using a silane coupling agent as an adhesive tackifier and to improve the compatibility between materials.
[0008] Component A includes epoxy silicone oil, thermal conductive powder, coupling agent, tin catalyst, and amine catalyst; Component B includes plasticizer, thermal conductive powder, reinforcing agent, crosslinking agent, and silane coupling agent;
[0009] The object of the present invention is achieved by the following measures, wherein the raw material parts mentioned are all weight parts unless otherwise specified, and the formula components of the two-component thermal conductive potting glue are as follows:
[0010]
[0011]
[0012] The epoxy silicone oil is at least one of epoxy-terminated polydimethylsiloxane, epoxy-side polydimethylsiloxane, and epoxy-terminated and epoxy-side polydimethylsiloxane, preferably epoxy-terminated and epoxy-side polydimethylsiloxane.
[0013] The structural formula of the terminal epoxy polydimethylsiloxane is shown in formula (1);
[0014]
[0015] The pendant epoxy polydimethylsiloxane has a structural formula as shown in formula (II);
[0016]
[0017] The first cross-linking agent is at least one of aminoalkyl-modified alkyl siloxane, N-(B-aminoethyl)-Y-aminopropyltrimethoxysilane oligomer, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 1,3-cyclohexanedimethylamine, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 1,2-cyclohexanediamine, isophoronediamine, 4,4'-diaminodicyclohexylmethane, 4,4'-diaminodiphenylmethane, methylcyclopentanediamine, o-diaminomethylcyclopentane, polyether primary amine, phenolic amine, ethylenediamine, diethylenetriamine, triethylenetetramine, metaphenylenediamine, bis-[-(trimethoxysilyl)-propyl]-ethylenediamine, bis-[3-(triethoxysilyl)-propyl]-ethylenediamine, and metaphenylenediamine.
[0018] The second crosslinking agent is at least one of methyltrimethoxysilane, methylphenyldimethoxysilane, methylphenyltriethoxysilane, methyl orthosilicate, propyl orthosilicate, methyltriethylsilane, methylpropyldimethoxysilane, methylpropyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, methylvinyldimethoxysilane, polymethyltrimethoxysilane, polymethyltriethoxysilane, polypropyltrimethoxysilane, 1,2-bis(trimethoxysilyl)ethane, and 1,2-bis(triethoxysilyl)ethane.
[0019] The plasticizer is at least one of polydimethyl silicone oil and epoxy-terminated silicone oil;
[0020] The thermally conductive powder is at least one of silicon powder, magnesium oxide, zinc oxide, aluminum nitride, boron nitride, aluminum oxide, aluminum hydroxide, and zinc hydroxide.
[0021] The silane coupling agent is aminoalkyl modified siloxane oligomer, γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, bisaminotriethoxysilane, γ-methacryloxypropyl trimethoxysilane, N,N-dimethylpropylene diaminopropyl methyl dimethoxysilane, vinyl tris (2-methoxyethoxy) silane, bisamino hydrolyzed oligomer, γ-aminopropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl triethoxysilane, N-[3 (trimethoxysilyl)-propyl] n-butylamine, N,N-dimethyl-3-aminopropyl trimethoxy Silane, N-n-butyl-3-aminopropyltriethoxysilane, 3-(diethylenetriamino)propyltrimethoxysilane, γ-(2,3 epoxypropoxy)propyltrimethoxysilane, γ-(2,3 epoxypropoxy)propyltriethoxysilane, 2(3,4 epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4 epoxycyclohexyl)ethyltriethoxysilane, 2-cyanoethyltriethoxysilane, ureidopropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, isocyanatepropyltrimethoxysilane, isocyanatepropyltriethoxysilane, mercaptomethyltriethoxysilane, hexadecyltrimethoxysilane.
[0022] The catalyst includes a tin catalyst and an amine catalyst;
[0023] The tin catalyst is at least one of stannous octoate, dibutyltin dilaurate, dibutyltin diacetate, and chelated tin.
[0024] The amine catalyst is at least one of caprolactam, triethylamine and bis-N,N'-(methyl-butylmethylene)-diethylenetriamine.
[0025] The epoxy value of the terminal epoxy silicone oil, the side epoxy silicone oil or the terminal side epoxy silicone oil is one or more of 0.1, 0.3, 0.6, 0.9, and the viscosity value is 100-750cp; preferably, the epoxy value is 0.6, 0.9, and the viscosity value is preferably 300cp.
[0026] The effective component of the first crosslinking agent is greater than 95%, and is preferably at least one of aminoalkyl-modified siloxane oligomer and N-(B-aminoethyl)-Y-aminopropyltrimethoxysilane oligomer.
[0027] The effective component of the second crosslinking agent is greater than 95%, and is preferably one or more of vinylmethoxysilane, tetrapropoxysilane, and ethyl orthosilicate.
[0028] The viscosity of the polydimethyl silicone oil and the epoxy-terminated silicone oil is 25-350 cp, and polydimethyl silicone oil is preferred, with a preferred viscosity of 100 cp.
[0029] The thermally conductive powder is preferably silicon powder or alumina, and has an average particle size of 3 μm-30 μm.
[0030] The silicon micropowder is of the type of spherical silicon micropowder, angular silicon micropowder, active silicon micropowder, and ultrafine silicon micropowder, preferably at least one of spherical silicon micropowder and active silicon micropowder, and has a particle size of 3 μm-10 μm.
[0031] The alumina is spherical alumina, square alumina, or strip alumina, and has a particle size of 5 μm-30 μm.
[0032] The silane coupling agent is effective at >95%; preferably one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0033] The tin catalyst is preferably dibutyltin dilaurate and chelated tin.
[0034] The amine catalyst is preferably bis-N,N'-(methyl-butylmethylene)-diethylenetriamine;
[0035] The potting glue of the present invention is prepared by the following production steps:
[0036] Component A: Add epoxy silicone oil to the planetary machine, add thermal conductive powder in four batches, stir and disperse at high speed, add coupling agent, continue stirring for 20-30 minutes, heat to 120℃, vacuum and degas for 2 hours; cool, add tin catalyst and stir for 5-10 minutes, add amine catalyst and stir and disperse for 5-10 minutes to discharge;
[0037] Component B: Add plasticizer to the planetary machine, add thermal conductive powder in four batches, heat to 120℃ for dehydration for 2h, cool, add cross-linking agent, stir for 5-15min, add coupling agent, stir and disperse for 5-10min and discharge.
[0038] The present invention has but is not limited to the following beneficial effects:
[0039] 1. Good adhesion, thermal conductivity, electrical insulation and storage properties;
[0040] 2. Less additives are used, lower VOC emissions, and no corrosion to materials;
[0041] 3. The cross-linking method is different from the ordinary condensation type. It contains a large number of cross-linkable active groups, has high activity and a faster curing speed than the condensation type. The difference in curing speed is more obvious under low temperature environment, and the curing speed of this product is faster under high temperature;
[0042] 4. Non-polluting, meeting the pollution requirements of Part 20 of GB / T13477.20-2002 "Test Methods for Building Sealing Materials";
[0043] 5. Environmentally friendly products, products comply with RoHS directive and REACH regulations.
[0044] Specific implementation methods
[0045] The specific implementation methods of the present invention are explained with the aid of examples. Except that the technology used for detection does not impose any form of limitation on the present invention, some schemes in the described embodiments belong to part of the embodiments of the invention. The embodiments obtained by ordinary technical operators in this field without creative results all belong to the protection scope of the present invention.
[0046] Embodiment 1:
[0047] This embodiment provides a fast-curing two-component thermally conductive potting adhesive, comprising the following components AB in parts by weight:
[0048] Component A is composed of 17 parts of end-epoxy polydimethylsiloxane (epoxy value 0.6, viscosity 300cp), 34 parts of spherical alumina (average particle size 15μm), 25 parts of spherical alumina (average particle size 5μm); 17 parts of square alumina (average particle size 15μm), 4 parts of hexadecyltrimethoxysilane, 1 part of dibutyltin dilaurate, and 2 parts of triethylamine.
[0049] 20 parts of polydimethylsilicone oil (viscosity 100cp), 29 parts of spherical alumina (average particle size 15μm), 22 parts of spherical alumina (spherical aluminum, average particle size 5μm); 21 parts of square alumina (average particle size 15μm), 4.5 parts of aminoalkyl modified alkylsiloxane oligomer, 1.5 parts of vinyltrimethoxysilane, 1 part of γ-aminopropyltriethoxysilane, 1 part of γ-glycidyloxypropyltrimethoxysilane, stir and mix to form component B.
[0050] Embodiment 2:
[0051] This embodiment provides a fast-curing two-component thermally conductive potting adhesive, comprising the following components AB in parts by weight:
[0052] Component A is composed of 17 parts of terminal epoxy polydimethylsiloxane (epoxy value 0.6, viscosity 300cp), 76 parts of spherical alumina (average particle size 5μm), 4 parts of hexadecyltrimethoxysilane, 1 part of chelated tin, and 2 parts of triethylamine.
[0053] Component B is composed of 20 parts of polydimethylsilicone oil (viscosity 100cp), 72 parts of spherical alumina (spherical aluminum, average particle size 5μm), 4 parts of aminoalkyl modified alkylsiloxane oligomer, 1 part of vinyltrimethoxysilane, 2 parts of γ-aminopropyltriethoxysilane, and 2 parts of γ-glycidyloxypropyltrimethoxysilane.
[0054] Embodiment 3:
[0055] This embodiment provides a fast-curing two-component thermally conductive potting adhesive, comprising the following components AB in parts by weight:
[0056] Component A is composed of 18 parts of end-epoxy polydimethylsiloxane (epoxy value 0.9, viscosity 100cp), 20 parts of spherical alumina (average particle size 15μm), 35 parts of spherical alumina (spherical aluminum, average particle size 5μm); 20 parts of square alumina (average particle size 15μm), 4 parts of hexadecyltrimethoxysilane, 1 part of chelated tin, and 2 parts of bis-N,N'-(methyl-butylmethylene)-diethylenetriamine.
[0057] Component B is composed of 20 parts of polydimethylsilicone oil (viscosity 100cp), 41 parts of active silicon powder (average particle size 5μm), 29 parts of square alumina (average particle size 15μm), 4.5 parts of aminoalkyl modified alkylsiloxane oligomer, 1 part of tetraethyl orthosilicate, 0.5 parts of tetrapropoxysilane, 1.5 parts of γ-aminopropyltriethoxysilane, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 1.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0058] Embodiment 4:
[0059] This embodiment provides a fast-curing two-component thermally conductive potting adhesive, comprising the following components AB in parts by weight:
[0060] Component A is composed of 13 parts of side epoxy polydimethylsiloxane (epoxy value 0.6, viscosity 300cp), 6 parts of terminal epoxy silicone oil (epoxy value 0.9, viscosity 350cp), 40 parts of spherical alumina (spherical alumina, average particle size 5μm); 33 parts of square alumina (average particle size 15μm), 5 parts of hexadecyltrimethoxysilane, 1 part of dibutyltin dilaurate, and 2 parts of bis-N,N'-(methyl-butylmethylene)-diethylenetriamine.
[0061] Component B is composed of 20 parts of polydimethylsilicone oil (viscosity 100cp), 26 parts of spherical alumina (average particle size 15μm), 21 parts of silica powder (spherical silicon, average particle size 10μm); 18 parts of square alumina (average particle size 15μm), 1 part of tetrapropoxysilane, 2 parts of vinyltrimethoxysilane, 3 parts of aminoalkyl-modified alkylsiloxane oligomer, 2 parts of side hydrogenated silicone oil, 2 parts of γ-aminopropyltriethoxysilane, and 2 parts of γ-glycidyloxypropyltrimethoxysilane.
[0062] Control group 1:
[0063] This embodiment provides a fast-curing two-component thermally conductive potting adhesive, comprising the following components AB in parts by weight:
[0064] Component A is composed of 17 parts of vinyl silicone oil (viscosity 350cp), 35 parts of spherical alumina (average particle size 15μm), 26 parts of spherical alumina (spherical aluminum, average particle size 5μm); 18 parts of square alumina (average particle size 15μm), 3 parts of hexadecyltrimethoxysilane, and 0.1 parts of platinum catalyst.
[0065] 23 parts of polydimethylsilicone oil (viscosity 100cp), 30 parts of spherical alumina (average particle size 15μm), 21 parts of spherical alumina (spherical aluminum, average particle size 5μm); 20 parts of square alumina (average particle size 15μm), 5.5 parts of hydrogen-containing silicone oil, and 0.6 parts of acetylene alcohol are stirred and mixed to form component B.
[0066] Control group 2:
[0067] This embodiment provides a fast-curing two-component thermally conductive potting adhesive, comprising the following components AB in parts by weight:
[0068] Component A is composed of 17 parts of hydroxyl silicone oil (viscosity 350cp), 35 parts of spherical alumina (average particle size 15μm), 26 parts of spherical alumina (spherical aluminum, average particle size 5μm), 18 parts of square alumina (average particle size 15μm), 2.2 parts of hexadecyltrimethoxysilane, and 0.8 parts of dibutyltin dilaurate.
[0069] 20 parts of polydimethylsilicone oil (viscosity 100cp), 30 parts of spherical alumina (average particle size 15μm), 21 parts of spherical alumina (spherical aluminum, average particle size 5μm); 20 parts of square alumina (average particle size 15μm), 1 part of vinyltrimethoxysilane, 3 parts of tetrapropylmethoxysilane, 2 parts of complex alcohol type crosslinking agent, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 2 parts of γ-aminopropyltriethoxysilane.
[0070] Example 5
[0071] Preparation method and performance testing
[0072] The component formulas of Examples 1-4 are prepared by the following method:
[0073] Component A: Add epoxy silicone oil to the planetary machine, add alumina in four batches, stir and disperse at high speed, add coupling agent, continue stirring for 20-30 minutes, heat to 120℃, vacuum and degas for 2 hours; cool, add tin catalyst and stir for 5-10 minutes, add amine catalyst and stir and disperse for 5-10 minutes to discharge;
[0074] Component B: Add plasticizer to the planetary machine, add thermal conductive powder in four batches, heat to 120℃ for dehydration for 2h, cool, add the first and second cross-linking agents, stir for 5-15min, add coupling agent, stir and disperse for 5-10min and discharge.
[0075] Performance testing:
[0076] Referring to the detection method in HG / T 5053-2016 "Silicone Potting Adhesive", the products of the embodiment and the control group were tested. The product performance is shown in the following table, specifically:
[0077] Control group 1 is a platinum-catalyzed addition-type potting adhesive. The product was poisoned after contacting the substances in the welding parts, did not cure, and had poor product applicability.
[0078] Control group 2 is a condensation-type potting adhesive. At 23°C and 80°C, the curing time is very long and cannot meet the requirements of rapid curing, affecting the efficiency of industrial production.
[0079] Performance test results table
[0080]
Claims
1. A fast-curing two-component thermally conductive potting adhesive, characterized in that The composition comprises the following components by weight:
2. The fast-curing two-component thermally conductive potting adhesive according to claim 1, characterized in that: The epoxy silicone oil is at least one of epoxy-terminated polydimethylsiloxane, epoxy-side polydimethylsiloxane, and epoxy-terminated polydimethylsiloxane.
3. The fast-curing two-component thermally conductive potting adhesive according to claim 2, characterized in that: The structural formula of the terminal epoxy polydimethylsiloxane is shown in formula (1); The pendant epoxy polydimethylsiloxane has a structural formula as shown in formula (II); 4. The fast-curing two-component thermally conductive potting adhesive according to claim 1, characterized in that: The first crosslinking agent is at least one of aminoalkyl-modified alkylsiloxane, N-(B-aminoethyl)-Y-aminopropyltrimethoxysilane oligomer, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 1,3-cyclohexanedimethylamine, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 1,2-cyclohexanediamine, isophoronediamine, 4,4'-diaminodicyclohexylmethane, 4,4'-diaminodiphenylmethane, methylcyclopentanediamine, o-diaminomethylcyclopentane, polyether primary amine, phenolic amine, ethylenediamine, diethylenetriamine, triethylenetetramine, m-phenylenediamine, bis-[-(trimethoxysilyl)-propyl]-ethylenediamine, bis-[3-(triethoxysilyl)-propyl]-ethylenediamine, etc.; The second crosslinking agent is at least one of methyltrimethoxysilane, methylphenyldimethoxysilane, methylphenyltriethoxysilane, methyl orthosilicate, propyl orthosilicate, methyltriethylsilane, methylpropyldimethoxysilane, methylpropyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, methylvinyldimethoxysilane, polymethyltrimethoxysilane, polymethyltriethoxysilane, polypropyltrimethoxysilane, 1,2-bis(trimethoxysilyl)ethane, and 1,2-bis(triethoxysilyl)ethane.
5. The fast-curing two-component thermally conductive potting adhesive according to claim 1, characterized in that: The plasticizer is at least one of polydimethyl silicone oil and epoxy-terminated silicone oil; The thermally conductive powder is at least one of silicon powder, magnesium oxide, zinc oxide, aluminum nitride, boron nitride, aluminum oxide, aluminum hydroxide, and zinc hydroxide.
6. The fast-curing two-component thermally conductive potting adhesive according to claim 1, characterized in that: The coupling agent is aminoalkyl modified siloxane oligomer, γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, bisaminotriethoxysilane, γ-methacryloxypropyl trimethoxysilane, N,N-dimethylpropylene diaminopropyl methyl dimethoxysilane, vinyl tris (2-methoxyethoxy) silane, bisamino hydrolyzed oligomer, γ-aminopropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl triethoxysilane, N-[3 (trimethoxysilyl)-propyl] n-butylamine, N,N-dimethyl-3-aminopropyl trimethoxysilane, One or more of alkyl, N-n-butyl-3-aminopropyltriethoxysilane, 3-(diethylenetriamine)propyltrimethoxysilane, γ-(2,3 epoxypropoxy)propyltrimethoxysilane, γ-(2,3 epoxypropoxy)propyltriethoxysilane, 2(3,4 epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4 epoxycyclohexyl)ethyltriethoxysilane, 2-cyanoethyltriethoxysilane, ureidopropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, isocyanatepropyltrimethoxysilane, isocyanatepropyltriethoxysilane, mercaptomethyltriethoxysilane, and hexadecyltrimethoxysilane.
7. The fast-curing two-component thermally conductive potting adhesive according to claim 1, characterized in that: The thermally conductive powder is at least one of silicon powder and aluminum oxide, and the average particle size of the thermally conductive powder is 3 μm-30 μm; The silicon micropowder is at least one of spherical silicon micropowder, angular silicon micropowder, active silicon micropowder and ultrafine silicon micropowder.
8. The fast-curing two-component thermally conductive potting adhesive according to claim 1, characterized in that: The alumina is spherical alumina, square alumina, or strip alumina, and has a particle size of 5 μm-30 μm.
9. The fast-curing two-component thermally conductive potting adhesive according to claim 1, characterized in that: The tin catalyst is at least one of stannous octoate, dibutyltin dilaurate, dibutyltin diacetate, and chelated tin; The amine catalyst is at least one of caprolactam, triethylamine and bis-N,N'-(methyl-butylmethylene)-diethylenetriamine.
10. The method for preparing the fast-curing two-component thermally conductive potting adhesive according to any one of claims 1 to 9, characterized in that The steps include: Component A: Add epoxy silicone oil to the planetary machine, add alumina in four batches, stir and disperse at high speed, add coupling agent, continue stirring for 20-30 minutes, heat to 120℃, vacuum and degas for 2 hours; cool, add tin catalyst and stir for 5-10 minutes, add amine catalyst and stir and disperse for 5-10 minutes to discharge; Component B: Add plasticizer to the planetary machine, add thermal conductive powder in four batches, heat to 120℃ for dehydration for 2h, cool, add the first cross-linking agent and the second cross-linking agent, stir for 5-15min, add coupling agent, stir and disperse for 5-10min and discharge.
Citation Information
Patent Citations
Transparent fire-proof pouring sealant composition
CN106751879A
Two-component pouring sealant and preparation method thereof
CN107325782A
Two-component fast-curing epoxy modified organic silicon adhesive and preparation method thereof
CN118185558A
Organic silicon adhesive for battery energy storage station
CN118725816A